Research of mineral composition of Populus angulate ait. - Borodina, Nataliia; Goncharov, Oleksandr; Gryshyna, Olena (Annals of Mechnikov’s Institute, 2025)
RESEARCH OF MINERAL COMPOSITION OF POPULUS ANGULATA AIT. Introduction. In recent years, the significance of forest plantations and restored forests has been steadily increasing, as poplar raw materials (Populus spp., family Salicaceae Mirb.) have become an increasingly attractive source of bioenergy and a promising renewable resource for biotechnology and bioprocessing projects. Particular attention is given to poplars of the Aigeiros Duby section, as species, clones, and varieties from this group are most commonly used in plantation cultivation. This creates promising opportunities for the rational and sustainable use of poplar-derived medicinal plant raw materials. Consequently, pharmacognostic studies of "black poplars," including research on the mineral composition of Populus angulata Ait. raw materials, are highly relevant. Such studies play a crucial role in standardization the raw materials. Aim. Study of the mineral composition of shoots, leaves and buds of Populus angulata Ait, and to determine total ash content in this raw material. Materials and methods. The objects of the study were shoots, leaves, buds of Populus angulata Ait. section black poplar Aigeiros Duby, family Salicaceae Mirb. The mineral composition analysis was carried out on the basis of the State Scientific Institution "Institute for Single Crystals" of the National Academy of Sciences of Ukraine (Kharkiv). Macro- and microelement composition of the raw material was determined by atomic emission spectrometry with photographic registration. The total ash content in the raw material Populus angulata Ait. by the gravimetric method according to the State Pharmacopoeia of Ukraine 2.0. Results. For the first time, the content of 19 mineral elements was determined by atomic absorption spectrometry in the raw material of Populus angulata Ait., cultivated in Ukraine, 5 of which are classified as macro- (K, Na, Ca, P, Mg) and 14 as microelements (Fe, Mn, Al, Si, Zn, Mo, Cu, Pb, Sr, Co, Ni, As, Cr, Hg), 10 of which are essential. It was established that the raw material of Populus angulata Ait. in terms of the content of heavy metals and total ash meets the requirements of the State Pharmacopoeia of Ukraine 2.0. The obtained data will contribute to further research and the development of quality control methods for poplar raw materials. Keywords: Populus angulata Ait., atomic emission spectrometry, mineral elements